Recent Progress in Using Graphene as an Ultrathin Transparent Support for Transmission Electron Microscopy. Issue 4 (15th January 2021) - Sinha, Sapna; Warner, Jamie H.
Abstract : Transmission electron microscopy (TEM) has long been used as the ultimate characterization technique for nanomaterials at the atomic level. Herein, the importance of the use of graphene in TEM is also presented to introduce the properties that make it indispensable for the characterization of other nanomaterials and study their properties and van der Waals interactions. A broad overview of the importance of using TEM for the study of nanomaterials and the rise of graphene as a superior substrate for the study of different kinds of low‐dimensional materials is provided. A review of the study of morphology, properties, and behavior of a range of nanomaterials is presented, with a specific focus on how graphene facilitates these studies due to its unique influence and interaction with the specific materials under TEM. This review presents an overview of the various studies and characterization that have been carried out on a range of nanomaterials using TEM with the use of graphene, and discusses the future challenges and engineering applications. Abstract : Graphene as the ultimate electron transparent support for transmission electron microscopy is reviewed, showing how weak scattering molecules and nanomaterials can be supported and imaged with structure resolved with contrast improvements beyond conventional carbon supports. Graphene supports enable direct imaging using lower doses and opens opportunities to study delicate molecules.